2009
DOI: 10.1515/reveh.2009.24.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxic Effects and Biomarkers of Lead Exposure: A Review

Abstract: Biological monitoring techniques are useful for risk assessment of toxic agents in the field of environmental health. Lead, a systemic toxicant affecting virtually every organ system, primarily affects the central nervous system, particularly the developing brain. Consequently, children are at a greater risk than adults of suffering from the neurotoxic effects of lead. The ability of lead to pass through the blood-brain barrier is due in large part to its ability to substitute for calcium ions. Within the brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
432
3
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 729 publications
(486 citation statements)
references
References 161 publications
5
432
3
2
Order By: Relevance
“…l ead is a known potent neurotoxicant with effects on cognition, behavior, and intelligence quotient (IQ) (1). The Centers for Disease Control and Prevention (CDC) and the American Academy of Pediatrics recommend screening all children for lead toxicity starting at age one.…”
mentioning
confidence: 99%
“…l ead is a known potent neurotoxicant with effects on cognition, behavior, and intelligence quotient (IQ) (1). The Centers for Disease Control and Prevention (CDC) and the American Academy of Pediatrics recommend screening all children for lead toxicity starting at age one.…”
mentioning
confidence: 99%
“…[26] Pb has been reported to cause significant neuronal damage in the CNS. [27][28][29] Although the use of Pb has been significantly reduced, Pb exposure continues to be a risk, because level of Pb is constantly stable in the environment and no unhazardous threshold for Pb exposure has been established. [3,30] The effects of Pb are particularly damaging to the developing nervous system, causing potentially irreversible learning and behavior deficits.…”
Section: Discussionmentioning
confidence: 99%
“…It is most vulnerable during development because of high rate of mitotic activity, cellular differentiation and synaptogenesis [8,9]. Pb has the ability to substitute Ca 2+ , it can, therefore, concentrate in the brain [10,11]. A recent study showed that majority of infants born in Kuwait during a two-month period in 2011 had blood Pb levels above the then established reference blood Pb level of 10 µg/dL [2].…”
Section: Introductionmentioning
confidence: 99%